2017
DOI: 10.1007/s00415-017-8432-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying ischemic stroke associated with cancer: a multiple model derived from a case–control analysis

Abstract: Ischemic stroke in patients with cancer is thought to be associated with a worse prognosis and might be the initial symptom of an unknown malignancy. However, diagnostic algorithms to reliably identify cancer-associated stroke have not been developed. In this retrospective single-centre analysis, 68 patients with ischemic stroke and an active solid malignancy were identified. Neurological assessment and outcome, cardiovascular risk factors, neuroimaging studies as well as laboratory findings were compared to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 24 publications
7
34
1
Order By: Relevance
“…In this study, most NHLAIS patients had experienced ischemic stroke within 6 months after the diagnosis of NHL. Radiologically, they all had multiple vascular infarcts with a past history of ischemic stroke, which is consistent with the findings of previous studies [1,[18][19][20], highlighting the similar features that NHLAIS and CaIS patients would probably likely experience.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, most NHLAIS patients had experienced ischemic stroke within 6 months after the diagnosis of NHL. Radiologically, they all had multiple vascular infarcts with a past history of ischemic stroke, which is consistent with the findings of previous studies [1,[18][19][20], highlighting the similar features that NHLAIS and CaIS patients would probably likely experience.…”
Section: Resultssupporting
confidence: 88%
“…In addition, the multivariate analysis demonstrated that elevated levels of both FIB and D-dimer were independent risk factors for NHLAIS. However, elevated levels of FIB and D-dimer are reported to be biomarkers of the hypercoagulable state seen in patients with cancer [2,6], the pathogenesis of which has also been reported by several studies related to ischemic stroke [6,18,20,21]. Furthermore, Seok and colleagues [22] found an elevated D-dimer level linearly correlates to the frequency of microembolic signals in the internal carotid on transcranial Doppler ultrasound in cancer patients and patients with cryptogenic stroke.…”
Section: Resultsmentioning
confidence: 77%
“…24 Potential biomarkers for occult cancer in stroke patients include elevated D-dimer, fibrinogen, and C-reactive protein; infarction in multiple vascular territories; and poor nutritional status. [24][25][26][27][28][29] Most comorbid cancers in stroke patients are solid tumors of the lung, gastrointestinal tract, and breast. [30][31][32] In addition, most patients with cancer and stroke are elderly and male, although patients of any age, sex, or race/ethnicity can be affected.…”
Section: Cancer Incidence In Stroke Patientsmentioning
confidence: 99%
“…This risk of incident, previously occult cancer appears highest in patients with cryptogenic stroke, in whom it is conceivable that the cancer caused or triggered the stroke through hypercoagulability . Potential biomarkers for occult cancer in stroke patients include elevated D‐dimer, fibrinogen, and C‐reactive protein; infarction in multiple vascular territories; and poor nutritional status . Most comorbid cancers in stroke patients are solid tumors of the lung, gastrointestinal tract, and breast .…”
Section: Epidemiologymentioning
confidence: 99%
“…13,53 The principal lesion patterns on DWI are multiple small cortical lesions extending to multiple vascular territories (in about 40% 13,54 ) and multi-staged acute and subacute ischemic lesions. 55,56 The level of D-dimer, a plasmin-derived degradation product of cross-linked fibrin, is a direct measure of activated coagulation. In cancer-related stroke, hypercoagulability as assessed by serial D-dimer levels was associated with early neurological deterioration, stroke recurrence and poor survival after stroke in patients with active cancer, suggesting that D-dimer level can be used in monitoring the effect of anticoagulation therapy.…”
Section: Detection Of Coagulopathymentioning
confidence: 99%